2022
DOI: 10.1039/d2dt00423b
|View full text |Cite
|
Sign up to set email alerts
|

Halo complexes of gold(i) containing glycoconjugate carbene ligands: synthesis, characterization, cytotoxicity and interaction with proteins and DNA model systems

Abstract: New neutral carbene complexes of gold(I) [Au(Im-Me)X] (X= Cl, Au1; X= Br, Au2; X= I, Au3) have been synthesized and fully characterized by different techniques, including NMR, UV-vis absorption spectroscopy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…[12] The pivotal role of the base, the reaction mechanism, and the wide scope of NHC ligands have been studied in detail by Nolan and co-workers among others, making such gold-NHC complexes accessible to a broad audience, expanding their applications in different areas of research and consolidating their role as the foundations of organogold synthesis. The chloride ligand present on gold can be easily replaced by other halides (halogen metathesis, see Scheme 2A) [13] as well as by a wide range of organic and inorganic ligands as will be discussed in the following sections. Emphasis will be placed on how the properties of the final complexes and their applications strongly depend on the nature of the "actor" ligand.…”
Section: [Au(nhc)x] Complexes (X = Halide)mentioning
confidence: 99%
See 1 more Smart Citation
“…[12] The pivotal role of the base, the reaction mechanism, and the wide scope of NHC ligands have been studied in detail by Nolan and co-workers among others, making such gold-NHC complexes accessible to a broad audience, expanding their applications in different areas of research and consolidating their role as the foundations of organogold synthesis. The chloride ligand present on gold can be easily replaced by other halides (halogen metathesis, see Scheme 2A) [13] as well as by a wide range of organic and inorganic ligands as will be discussed in the following sections. Emphasis will be placed on how the properties of the final complexes and their applications strongly depend on the nature of the "actor" ligand.…”
Section: [Au(nhc)x] Complexes (X = Halide)mentioning
confidence: 99%
“…The [Au(IPr)OH] can also be used for the preparation of [Au(IPr)H] (14) and [Au(IPr)(NTf 2 )] (15), in reactions performed at room temperature with trimethoxysilane and bis(trifluoromethylsulfonyl)imide, respectively. The conditions used for the preparation of [Au(IPr)(NTf 2 )] are also suitable for the C À H activation of terminal alkynes such as phenylacetylene, with the production of the corresponding gold-alkynyl complex (13).…”
Section: Table 1 Synthesis Of [Au(nhc)(oh)mentioning
confidence: 99%
“…The presence of a sugar residue in the coordination sphere can also favor solubility in water and provide modulable chirality. Recently, our group extensively investigated glycoconjugation to improve the selectivity of organometallic platinum­(II/IV) and gold­(I) , complexes. Notably, a Pt­(II) complex containing a glycoconjugated N- heterocyclic carbene ligand, [PtMe­(dmphen)­(ethene)­(NHC-glu)] + OTf (Figure ), was found to be extremely cytotoxic and selective to cancer cells with IC 50 values in the high nanomolar range.…”
Section: Introductionmentioning
confidence: 99%
“…As for point (a), the synthetic strategy provides robust and versatile compounds given the wide choice of carbohydrates, along with key-beneficial properties, such as chirality, tunability, hydrophilicity, and biocompatibility. Thus, Pd­(II) complexes containing ligands derived from simple hexoses have been successfully applied in asymmetric allylic alkylations under unconventional conditions, , and agents based on Pt­(II), Pt­(IV), and Au­(I) complexes showed high selectivity and activity toward anticancer cells. Furthermore, it has also been demonstrated that the simple shift of the coordinating functions between adjacent positions of the pyranoside structure allows the creation of pseudoenantiomeric ligands, thus enabling the promotion of the same reaction with opposite enantioselectivity. …”
Section: Introductionmentioning
confidence: 99%